PENGEMBANGAN BUKU AJAR ASTRONOMI BERBASIS SELF REGULATED LEARNING SEBAGAI UPAYA MEMOTIVASI MAHASISWA UNTUK BELAJAR MANDIRI - Susilawati -; Harry Soeprianto; Habibi - (Jurnal Penelitian Pendidikan IPA, 2015)
The study aims to produce a textbook Astronomy based self-regulated learning that can motivate students to learn independently. The method used is Research and Development (R & D) by adopting three of the four stages of development models that define 4D (definition), Design (design), and the Development (development). Define phase conducted to determine the characteristics of the products textbook developed through a preliminary study. Selection of the format of the manufacture of textbooks carried out at the stage of design to produce a draft of the Development Phase I. undertaken to produce draft II, III draft, and the final product of the textbook developed. Draft II obtained through the revision of expert validation of three validator recommended. Draft III is the result obtained from a test on a small group of 5 students FKIP Unram as samples taken at random. The end product obtained from the development of field tests on all Unram FKIP students who are taking elective courses astronomical TP 2013/2014 amounted to 12 people. Validation results as well as devices supporting textbook shows the criteria of "very decent" to be used and can motivate students to learn independently.